2010
DOI: 10.1007/s00277-010-1068-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute but not chronic graft-versus-host disease is associated with a reduction of circulating CD4+CD25highCD127low/− regulatory T cells

Abstract: Defects in central and peripheral tolerance are thought to contribute to life-threatening graft-versus-host disease (GvHD), a severe complication following allogeneic stem cell transplantation (SCT). Recent investigations have demonstrated regulatory T cells (Tregs) to suppress allogeneic immune reactions. Therefore, SCT patients with no or critically low numbers of Tregs may have an increased risk of GvHD. To address this hypothesis, we analyzed the recovery of CD4(+)CD25(high)CD127(low/-) Tregs in the periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…Therefore, increased availability of IL-7 may enhance peripheral expansion in response to both high-affinity and low-affinity antigens [8] and may promote alloreactivity to low-affinity minor antigens and thereby progression to aGVHD. In addition, elevated IL-7 levels may cause a functional shift within the T cell compartment, as IL-7 has minimal impact on the homoeostatic proliferation of regulatory T cells (Tregs) [33,43] that are thought to inhibit the development of aGVHD and found at reduced levels in patients with aGVHD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased availability of IL-7 may enhance peripheral expansion in response to both high-affinity and low-affinity antigens [8] and may promote alloreactivity to low-affinity minor antigens and thereby progression to aGVHD. In addition, elevated IL-7 levels may cause a functional shift within the T cell compartment, as IL-7 has minimal impact on the homoeostatic proliferation of regulatory T cells (Tregs) [33,43] that are thought to inhibit the development of aGVHD and found at reduced levels in patients with aGVHD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…56,62 Impaired Treg reconstitution appears predictive for subsequent chronic GVHD in some, but not all, studies. 57,[62][63][64][65] Analysis of Treg homeostasis after HSCT has shown that Treg deficiency after HSCT appears to result primarily from decreased thymic production of Tregs. Although there is a compensatory increased homeostatic proliferation of circulating memory Tregs, this is ultimately insufficient to prevent Treg deficiency, due in part to proliferation-induced telomere shortening, 66 enhanced death signaling, and apoptosis of rapidly dividing Treg.…”
Section: Inhibition Of Cytokine Receptor-mediated Signalingmentioning
confidence: 99%
“…8 However, literature regarding Tregs is still controversial, with a reduction in CD4 ϩ CD25 high CD127 low Tregs being associated with aGVHD but not cGVHD. 9 Clarke et al reported an increase of peripheral Tregs in patients with cGVHD. 10 More recently, Th17 ϩ T cells have also been implicated in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%